COSMOPOLITANISM AND THE SPECIFITY OF THE LOCAL IN WORLD LITERATURE - Lazarus, Neil (Porównania, 2013)
Taking its cue from recent scholarship de-linking the idea of “modernity” from the idea of “the West”, this article advocates the notion of “world literature” as the body of literature that has, in the last 150 to 200 years, registered and encoded the social logic of modernity. Building on Franco Moretti’s postulation of a single world-literary system (structured not merely by difference but also by inequality) and on the theoretical work of Fredric Jameson, the article traces some of the ways in which the local detail of peripheral modernity is represented in literary texts by Thomas Mofolo, Patrick Chamoiseau, Lao She, Rohinton Mistry, Ivan Vladislavić and others, demonstrating that there is no necessary contradiction between the ideas of the “universal” and the “local” or the “national”, but that, on the contrary, there are only local universalisms (and, for that matter, only “local cosmopolitanisms”), which it becomes the task of readers to situate as completely as they can.